Mandatory lane-changing decision making and planning in emergency situations. Issue 1 (24th December 2022) - Liu, Yang; Shi, Congling
Abstract: By considering mandatory lane-changing as a collision avoidance measure, this paper presented the corresponding lane-change decision making and trajectory planning algorithm under an emergency scenario. Different from the traditional algorithm in which lane-change decision making and trajectory planning are separated, they are here coupled in a proposed algorithm and the related parameters are dynamically adjusted in the whole process. In addition to lane-change collision avoidance feasibility analysis, lane-change time instance and duration time are obtained by solving the constrained convex quadratic optimization programme. By taking lane-change time instance and duration time as inputs, the algorithm then proceeded to propose a kinematic model-based high-order polynomial lane change trajectory. By giving the simulation result compassion with the related algorithm, it is proved that the proposed algorithm has a good robustness and high efficiency.